(untitled) (Research, Society and Development, 2021)
One of the challenges for patients with diabetes mellitus (DM) is to control glycemic concentrations and, there is an improvement in clinical results when using mobile applications to perform their self-care. Blood glucose monitoring by capillary technique provides only intermittent data on metabolic control, preventing a complete view of the patient’s glycemic profile. With Continuous Glucose Monitoring (MCG), it is possible to accurately assess glycemic variations throughout the day, with more effective therapeutic intervention. Given these premises, this research aimed to promote the development of a mobile application, called UP GLICEMIA, for glucose monitoring by CGM through the subcutaneous sensor and GC, which generate simultaneous graphical reports. The glycemic values when measured and registered in the application, are informed to the user in the form of alert patterns for normoglycemia, tolerable, hyperglycemia and hypoglycemia, presented in green, yellow, red and purple, respectively. This application also generates daily, weekly and monthly graphical reports for the two techniques of glycemic measurements by means of individual and associated graphs, which may assist in the therapeutic conduct. It was an applied, exploratory research for application development, with a new perspective for glycemic control. It is expected that the use of UP GLICEMIA for patients with type 1 and type 2 DM and by the health professional can help in a better understanding of the glucose monitoring of the user, demonstrating the glycemic profile completely and enabling glycemic control.